2007
DOI: 10.1063/1.2730568
|View full text |Cite
|
Sign up to set email alerts
|

Atomic ordering kinetics of FePt thin films: Nucleation and growth of L10 ordered domains

Abstract: To lower the L1 0 ordering temperature of FePt thin films, a detailed understanding of the nucleation and growth processes of L1 0 ordered domains is of particular importance. In the present study, a nucleation activation energy E n = ͑0.5− 0.6͒ ± 0.1 eV and a growth activation energy E g = 0.9± 0.1 eV for the L1 0 ordered domains in the FePt thin films are determined by studying the individual annealing-temperature dependence of the nucleation and growth parameters of the L1 0 ordered domains. These data make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…Farrow et al [13] has suggested, given sufficient undercooling, the nucleation may even be of a continuous type rather than a first-order phase transformation. Li et al [14] recently reported dark field transmission electron microscopy (TEM) images for FePt thin films annealed in time scales of seconds that indicated that the ordering initiated at the grain boundaries. Grain boundaries are sources and sinks for vacancy migration [15] which would assist in the diffusion processes necessary for atomistic rearrangement.…”
Section: Introductionmentioning
confidence: 97%
“…Farrow et al [13] has suggested, given sufficient undercooling, the nucleation may even be of a continuous type rather than a first-order phase transformation. Li et al [14] recently reported dark field transmission electron microscopy (TEM) images for FePt thin films annealed in time scales of seconds that indicated that the ordering initiated at the grain boundaries. Grain boundaries are sources and sinks for vacancy migration [15] which would assist in the diffusion processes necessary for atomistic rearrangement.…”
Section: Introductionmentioning
confidence: 97%
“…This conclusion is also supported by recent self-diffusion studies of 57 Fe in FePt films, 22 yielding a diffusion activation energy Q Fe = 1.65 eV, which is comparable with the activation energies E = 1.6-1.7 eV for the L1 0 ordering transition of FePt thin films. 7,9 In conclusion, based on activation volume measurements, atomic processes involved with the L1 0 -ordering phase transition in FePt thin films have been revealed. A thermal-vacancy-assisted ordering transition was observed in the thin films.…”
mentioning
confidence: 84%
“…7,9 For a phase transition via atomic diffusions mediated by defects, the activation volume consists of two terms, ⌬V ‫ء‬ = ⌬V f + ⌬V m , where ⌬V f , the formation volume, is the volume change upon the formation of one defect in its standard state, and ⌬V m , the migration volume, is the additional volume change for defect migration to the saddle point, which is of the order of ϳ10% of the average atomic volume ⍀. 11,19 For atomic diffusions mediated by thermal vacancies the ⌬V f becomes the predominant term, and ⌬V ‫ء‬ varies in the range of 0.5-1 ⍀.…”
mentioning
confidence: 99%
“…8͑b͔͒. Assuming that the rate constant t E −1 has an Arrhenius temperature dependence, we have [24][25][26][27] 9͒, indicating that the growth of the ␣-Fe and Nd 2 Fe 14 B nanocrystals in the amorphous matrix is a thermally activated process.…”
Section: Growth Of Nanocrystals In Amorphous Nd 9 Fe 85 B 6 Subjecmentioning
confidence: 96%